Cannabis-related hospitalizations before and after the legalization of recreational cannabis among children and youth in Manitoba, Canada - Taillieu, Tamara; Flaten, Lisa; Afifi, Tracie; Brownell, Marni; Enns, Jennifer; Katz, Laurence; Nickel, Nathan; Sareen, Jitender (International Journal of Population Data Science, 2026)
Background Research suggests that cannabis poisonings among children and youth may have increased with the legalization of cannabis, particularly among young children and in provinces that permit the sale of edibles. The current study examines cannabis-related hospitalizations before and after cannabis legalization among children and youth in Manitoba. Method We used administrative data housed at the Manitoba Centre for Health Policy to examine cannabis-related hospitalizations a) per 100,000 population, and b) per 1,000 all-cause hospitalizations. All Manitoba residents aged 0-18 years between 2013-2023 were included. Incidence rate ratios compared rates across time periods: pre-legalization (Jan. 2013-Oct. 2018), phase 1 (Oct. 2018-Dec. 2019), and phase 2 (Jan. 2020-Dec. 2023). Results The monthly mean number of cannabis-related hospitalizations was 8.50 (pre-legalization), 9.52 (phase 1), and 8.59 (phase 2). The mean age at time of hospitalization was 16.80 (pre-legalization), 16.53 (phase 1), and 16.86 (phase 2). Children less than 10 years represented 1.02% (pre-legalization), 4.35% (phase 1), and 2.39% (phase 2) of all cannabis-related hospitalizations. Although increases in annualized rates of cannabis-related hospitalizations per 100,000 population and per 1,000 all-cause hospitalization were noted in phase 1 relative to the pre-legalization period, these increases were not statistically significant (adjusted incident rate ratios 1.11 and 1.10, respectively). Conclusion The legalization of cannabis did not appear to increase the number of cannabis-related hospitalizations among children and youth in Manitoba. Nonetheless, it is important that public education materials stay focused on promoting the health and safety of children and youth in the context of cannabis legalization.